Prodigal son. The complete second season [videorecording (DVD)] - Fedak, Chris; Sklaver, Sam (Warner archives., 2021)
Malcolm Bright is a criminal profiler who gets inside the minds of killers because his father, Dr. Martin Whitly, was a notorious serial killer. Now he's using his twisted genius to help the NYPD solve murders. Season 2 picks up with Bright "taking care" of his sister after her shocking actions and protecting his mother from a secret that could tear the family apart.